1993
DOI: 10.1177/000348949310201208
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Metabolites in Experimental Otitis Media and Effects of Anti-Inflammatory Drugs

Abstract: Previous studies have shown that arachidonic acid (AA) metabolites are important in the pathogenesis of otitis media with effusion. The AA metabolites in 4 different experimental models for otitis media were analyzed, and the effect of anti-inflammatory drugs was studied. Purulent otitis media was induced in rats by inoculation of Streptococcus pneumoniae in the tympanic bulla, serous otitis media by blocking the tympanal orifice of the eustachian tube, and mucoid otitis media by combining the two procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…LTs and PGs are potent inflammatory mediators which may play a role in the formation of OME. Previous studies have shown that these metabolites are identified in OME such as 6-keto-PGF 1a , PGF 2a , TXB 2, PGE 2, PGD 2 , LTB 4 , LTC 4 , LTD 4, 5-HETE, 12-HETE, and 15-HETE [3,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTs and PGs are potent inflammatory mediators which may play a role in the formation of OME. Previous studies have shown that these metabolites are identified in OME such as 6-keto-PGF 1a , PGF 2a , TXB 2, PGE 2, PGD 2 , LTB 4 , LTC 4 , LTD 4, 5-HETE, 12-HETE, and 15-HETE [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…None of them has found any otoscopic difference between the naproxen and placebo group of patients with OME. Goldie et al [10] showed that indomethacine inhibits middle ear fluid accumulation in experimental model. Cutler et al [15] demonstrated that transtympanic steroid reduces middle ear effusion, whereas diclofenac has no effect on effusion in their experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites of AA have been identified in human MEE as well as in experimentally induced MEE in animals (58, 143, 144). Indomethacin or ibuprofen, an inhibitor of prostaglandin-forming cyclooxygenase, has been reported to be effective in reducing the accumulation of MEE or mucosal thickness in the animal OM model (145, 146). However, LTs seem to be more pro-inflammatory than PGs in otitis media, according to previous animal studies (58, 144).…”
Section: Inflammation and Ommentioning
confidence: 99%
“…Σε μελέτη των Goldie και συν. η πρόκληση μέσης ωτίτιδας με υγρό προκλήθηκε με απόφραξη της ΕΣ αρουραίων με γουταπέρκα και η αξιολόγηση της φλεγμονώδους αντίδρασης έγινε με μέτρηση των μεταβολιτών του αραχιδονικού οξέος (Goldie, 1993).…”
Section: 4unclassified
“…Η ΕΜΩ δεν παρουσιάζεται μόνο σαν νόσημα πολυπαραγοντικής αιτιολογίας αλλά και σαν νόσος με ποικίλη κλινική εμφάνιση, καλύπτοντας το φάσμα από ένα μεμονωμένο επεισόδιο μέχρι εμμένουσα φλεγμονή ανθεκτική σε κάθε είδους θεραπεία (Hurst D, 1990 (Jung, 1983). Φαίνεται λοιπόν, ότι το αραχιδονικό οξύ και οι μεταβολίτες του παίζουν κάποιο ρόλο στην παθογένεια της ΕΜΩ και μάλιστα έχει βρεθεί ότι σε οξείες μορφές οι LTC 4 και PGE 2 είναι οι ουσίες που προεξάρχουν, ενώ η παρουσία 6-keto PGF1α αποτελεί δείκτη χρονιότητας (Goldie, 1993 (Brunton, 1996). Μελέτη in vivo μοντέλου φλεγμονής του βλεννογόνου μέσου ωτός τσιντσιλά, με χρήση ισταμίνης ενδοτυμπανικά και μαγνητικής τομογραφίας, έδειξε ότι η προετοιμασία με ρανιτιδίνη δεν ανέστειλε την αγγειδιασταλτική δράση της ισταμίνης στα 40 λεπτά από την πρόκληση της φλεγμονής (Chan, 1994 (Babe, 1996).…”
Section: στατιστική ανάλυση δεδομένωνunclassified